Understanding the impact of introduction of Robinia pseudoacacia on community functional structure and moisture regulation in the Loess Plateau, China, using a trait-based approach - Zheng, Cheng; Yuan, Liuhuan; Shi, Haijing; Duan, Gaohui; Liu, Yangyang; Wen, Zhongming (Frontiers in Plant Science, 2024)
Depending on specific environmental conditions, Robinia pseudoacacia plantations can have a positive or negative impact on ecosystem function. Numerous studies have demonstrated that Robinia pseudoacacia plantations on the Loess Plateau has decreased the water levels in this area, increasing the risks of water resource security. Understanding the ecosystem function of the Robinia pseudoacacia plantations is thought to be critical to vegetation restoration in the Loess Plateau. However, no consensus exists on the mechanism by which afforestation affects moisture regulation under varying environmental conditions, nor on how to manage Robinia pseudoacacia plantations to maintain the ecosystem function. In this study, we used the response-effect trait approach to examine the evolving relationship between community functional composition and water regulation by collecting community samples from Robinia pseudoacacia plantations and natural ecosystems across three vegetation zones (steppe, foreststeppe and forest). Our goal was to clarify how the afforestation of Robinia pseudoacacia impacts functional composition and, consequently, moisture regulation. The findings indicated that Robinia pseudoacacia negatively impacts community structure and moisture regulation in the drier steppe and forest-steppe (P<0.05). Afforestation of Robinia pseudoacacia increases specific leaf area (SLA), leaf nitrogen content (LNC), and plant height (H), while weakening the trait correlations within the community, which is the main cause of the negative effect. Furthermore, we discovered that response and effect traits overlapped (leaf tissue density, LTD) in natural ecosystems but not in afforested ecosystems within the response-effect traits framework. In conclusion, our findings indicated that the functional structure of communities and moisture regulation are impacted Robinia pseudoacacia plantations in drier habitats.Additionally, because response-effect traits do not overlap and trait coordination declines, afforestation increases instability in the moisture regulation maintenance. The introduction of Robinia pseudoacacia weakens the coordination and coupling relationships between traits. We advise giving preference to native species over Robinia pseudoacacia for restoration in the dry steppe and forest-steppe zones. Trait-based restoration approaches can enhance the efficacy of restoration measure in achieving desired ecosystem functions.